2022
DOI: 10.1186/s12885-022-09684-0
|View full text |Cite
|
Sign up to set email alerts
|

Emodin inhibits invasion and migration of hepatocellular carcinoma cells via regulating autophagy-mediated degradation of snail and β-catenin

Abstract: Background Previous studies reported that emodin extracted from Rheum palmatum L. exerts antiproliferation and antimetastatic effects in a variety of human cancer types. However, the role of emodin in hepatocellular carcinoma (HCC) remain unknown. Methods EdU and colony formation assays were performed to evaluate the effects of emodin on proliferation. The mobility capacities of HCC treated with emodin were evaluated using wound healing assay. Tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 50 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…migrated rate (%) = (width of initial wound—width of remaining wound) / width of initial wound × 100 [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…migrated rate (%) = (width of initial wound—width of remaining wound) / width of initial wound × 100 [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Its mechanism involves the inhibition of the PI3K/AKT signaling pathway, facilitating the degradation of β‐catenin protein along with accumulated LC3 protein, thereby blocking the Wnt signaling pathway. This dual action inhibits the process of epithelial–mesenchymal transition (EMT) in HepG2 cells (Qin et al, 2022). In a study conducted by Zhang et al, Tetrandrine was observed to exert an inhibitory effect on the migration of HCC cells, which is closely associated with the induction of autophagy in human HCC cells.…”
Section: Natural Products Regulate Hcc Through Autophagymentioning
confidence: 99%
“…In hepatocellular carcinoma cells, emodin treatment activated autophagy and promoted autophagic flux, simultaneously reversed EMT, and indicated the correlation between EMT and autophagy. Both EMT and autophagy regulation were revealed to be attributed to the PI3K/AKT/mTOR pathway [ 114 ]. By regulating EMT, emodin could reduce cancer cell resistance to chemotherapeutic drugs, such as gemcitabine resistance in pancreatic cancer cells and doxorubicin resistance in small-cell lung cancer cells [ 115 , 116 ].…”
Section: Phytochemicals With the Effects Of Interfering Emtmentioning
confidence: 99%